2006
DOI: 10.1002/jso.20731
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of resection margin involvement after extended (D2/D3) gastrectomy for advanced gastric cancer: A 15‐year experience at a single institute

Abstract: Our results suggest that a positive microscopic margin is associated with a worse outcome in patients with node-negative disease. Therefore, a more aggressive treatment, such as re-operation, is needed in node-negative patients with a positive microscopic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
100
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 25 publications
10
100
2
3
Order By: Relevance
“…In analysis of 2,740 resected cases from Korea, 49 had a positive margin on final histology; survival time was similar (P ¼ 0.259) for positive (33 months median survival) and negative (37 months median survival) margin patients with node positive disease. In node negative patients, however, median survival was 174 months for negative margin resections and 37 months for patients with positive margins (P ¼ 0.0001), prompting the authors to conclude that more aggressive treatment, including reoperation, should be offered only to node negative patients with positive microscopic margins [96]. Kim et al [97] published similar findings: of D2/D3 dissection patients who had fewer than 6 LN involved with tumor, survival was significantly worsened by a microscopically positive margin.…”
Section: Intra-operative Decision-makingmentioning
confidence: 99%
“…In analysis of 2,740 resected cases from Korea, 49 had a positive margin on final histology; survival time was similar (P ¼ 0.259) for positive (33 months median survival) and negative (37 months median survival) margin patients with node positive disease. In node negative patients, however, median survival was 174 months for negative margin resections and 37 months for patients with positive margins (P ¼ 0.0001), prompting the authors to conclude that more aggressive treatment, including reoperation, should be offered only to node negative patients with positive microscopic margins [96]. Kim et al [97] published similar findings: of D2/D3 dissection patients who had fewer than 6 LN involved with tumor, survival was significantly worsened by a microscopically positive margin.…”
Section: Intra-operative Decision-makingmentioning
confidence: 99%
“…retropancreatic nodes or superior mesenteric nodes). Cho et al [19] reported their 15-year experience of extended gastrectomy for advanced gastric cancer. The median survival time of the positive margin group was 34 mo.…”
Section: Discussionmentioning
confidence: 99%
“…And when pancreaticoduodenal region is involved by advanced gastric cancer, combined PD and gastrectomy will bring the chance of tumor-free resection margin. And curative (R0) resection improves prognosis [19,20] . PD with gastrectomy will benefit the lymphadenectomy of No.…”
Section: Discussionmentioning
confidence: 99%
“…Em um estudo a incidência foi de 8,2% em 572 operações.9 Outro estudo detectou acometimento da margem proximal em 1% das 2740 gastrectomias subtotais avaliadas 4 . De Gara et al 5 demonstraram margem comprometida em 6% dos 121 pacientes estádio 1 e 2 da classificação TNM; 22% dos 132 pacientes com estádio 3 e 25% dos 60 pacientes com 4.…”
Section: Discussionunclassified
“…No entanto, também existe possibilidade de acometimento da margem cirúrgica proximal. Esse acometimento, mesmo que microscópico, cursa com redução na sobrevida 9,13,4 . Cho et al 4 demonstraram sobrevida média de 34 meses em 49 pacientes com margem comprometida e sobrevida de 69 meses em 2691 pacientes com margens livres.…”
unclassified